HUBUNGAN ANTARA SHIFT KERJA DENGAN KELELAHAN KERJA SUBYEKTIF PADA PENJAGA WARNET DI KELURAHAN SEKARAN (Unnes Journal of Public Health, 2015)
The purpose of this research is to determine the relationship between work shift and subjective fatigue of work at internet cafe operators in Sekaran. Shift work can affect variety of physical and psychological changes in the people including fatigue. Based on the result preliminary observation conducted on ten workers in internet cafe, are known to 100% of workers experiencing subjective fatigue. Which means, from 10 samples known to all workers experiencing fatigue of work. The research type is explanatory, with research method of cross sectional. The population of this research was 33 people, and by using the total sampling techniques. Research instruments such as questionneirs, weight scale, and microtoice. The data analysis was done using Fisher’s Exact Test with α =5%. The conclude of the research is there is not relation between work shift and subjective fatigue of work at internet cafe operators in Sekaran. Based on these result of the research, the suggestions are submitted (1) to employees can always apply the occupational health and safety (K3) well. (2) for owner, more respect to setting work hours and breaks for internet cafe operators,(3) for further researchers, was to try modifyng research by changing the type or the variables of research.